The effect of hyoscine butyl bromide on the active phase of labour among primiparous women delivered at the Jos University Teaching Hospital - George OC; Ajang MF; Anyaka CU (Ibom Medical Journal)
Background: Labour is a physiological process to expel products of conception to the external environment. More often than not, it results in the delivery of a healthy baby to a happy mother. However, it has also been associated with a significant number of adverse maternal and fetal outcomes. Over the years several steps and interventions have been taken to reduce these adverse outcomes. One of such intervention is the reduction of the duration of labour which has been found to improve neonatal outcomes. Hyoscine-Butyl Bromide has been shown to reduce the duration of labour, however, it is currently not recommended for labour intervention because no beneficial effects have been associated with its use yet and it remains an area prioritized for research.